2015
DOI: 10.1007/s00107-015-0947-4
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical properties of Eucalyptus grandis wood and transition age between the juvenile and mature woods

Abstract: The present study is aimed at evaluating the anatomical characteristics of Eucalyptus grandis wood and the transition age between the juvenile and mature woods. Four trees of 23-year-old E. grandis were used. The juvenile, transition and mature wood zones were found by fiber length measurement from the pith to the bark. Samples were taken from juvenile wood, transition wood and mature wood and the anatomical properties of the wood were determined. The results showed that: (1) the fiber length, cell wall thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
20
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 7 publications
8
20
0
3
Order By: Relevance
“…Present results showed that the slenderness ratio of the four pioneer species is in the range of 36.4-50.2. This result is comparable to the study for Eucalyptus grandis, as shown in Table 1, which ranges from 42.6 to 59.8 [22]. Batai, ludai, mahang, and sesendok also show thin fibre wall and large fibre lumen diameter which, according to [5] this features, contributes to the good adhesive penetration.…”
Section: Anatomical Propertiessupporting
confidence: 86%
“…Present results showed that the slenderness ratio of the four pioneer species is in the range of 36.4-50.2. This result is comparable to the study for Eucalyptus grandis, as shown in Table 1, which ranges from 42.6 to 59.8 [22]. Batai, ludai, mahang, and sesendok also show thin fibre wall and large fibre lumen diameter which, according to [5] this features, contributes to the good adhesive penetration.…”
Section: Anatomical Propertiessupporting
confidence: 86%
“…These differences during tree development will reflect in the formation of wood with different properties, which differentiate the juvenile and adult wood. In species of rapid growth, such as some members in the genus Eucalyptus, such differences may be more evident due to the more accelerated growth rate that marks the juvenile wood formation period (FANG;YANG, 2003;LEAL et al, 2003;RAMÍREZ et al, 2009;PALERMO et al, 2015 ). For., Piracicaba, v. 44, n. 111, p. 611-621, set.…”
Section: Evaluated Propertiesmentioning
confidence: 99%
“…The juvenile wood, produced in the first years of growth of the tree, differs from the mature wood, especially for presenting greater magnitude of variation in its technological properties, notably marked by sudden changes in cellular composition (ZOBEL;VAN BUIJTENEN, 1989;BAO et al, 2001;CALONEGO et al, 2005;PALERMO et al, 2015) and this almost always has a negative effect on the wood quality. Tsuchiya and Furukawa (2009), Fan et al (2009) and Apiolaza et al (2013) emphasize that studies that evaluate the radial and axial variation in the trunk, besides enabling an understanding of the architecture adopted by different species to make water transport become efficient and secure, demonstrate extreme commercial importance, because from the results it is possible to predict which raw material is commercially the most indicated for a particular application.…”
Section: Introductionmentioning
confidence: 99%
“…The definition of the age at which the species makes the transition from juvenile wood to adult wood has been evaluated in several studies (Bal & Bektas, 2013, Palermo et al, 2015, Zanuncio et al, 2017. Evidently, adult wood is the aim of study of this research.…”
Section: Introductionmentioning
confidence: 99%